Modification of Handball Learning Using Plastic Balls at Pakusari State High School Enchacing Learning Outcomes - Sunyoto, Sintya Martha Rahayu; Apriliyanto, Rizki; Bahriyanto, Ahmad (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
This study aims to determine the effectiveness of hand ball learning modifications using plastic balls in improving student learning outcomes in the subjects of Physical Education, Sports, and Health (PJOK). The action hypothesis in this study is that the use of plastic balls as a learning modification medium can improve the learning outcomes of students' handball skills. The main premise of the study is because handball learning in schools often faces the constraints of limited means, low media variation and a lack of courage for students to perform basic game techniques. Plastic balls were chosen because they are lighter, safer, easy to obtain and suitable for learning needs of basic skills such as passing, dribbling, catching, and shooting. This study uses the design of Class Action Research (PTK) which is carried out through the pre-cycle, cycle I, and cycle II stages. The subjects of the study were 36 students in grades XII-1 of SMA Negeri Pakusari. Data was collected through observation and handball skill tests, then analyzed descriptively based on average scores, number of students completed, and percentage of learning completion. The results of the study showed a gradual increase in learning outcomes. In the pre-cycle, the students who achieved completeness amounted to 19 students or 52.78% with an average class of 75.94. After the action in the first cycle, the completeness increased to 27 students or 75.00% with an average class of 80.28. In cycle II, the completeness reached 33 students or 91.67% with an average class of 88.78. Improvements also occur in all aspects of skills, namely passing, dribbling, catching, and shooting. Thus, the hypothesis of action is accepted. Modification of handball learning using plastic balls has proven to be effective as a safe, adaptive, and practical learning strategy to improve student learning outcomes in PJOK. Keywords: handball; plastic balls; learning outcomes; learning modifications; Physical Education.